The Role of English Training Camp in Improving Students’ Speaking Skill - Rahmadiani, Sukma; Mahyuni; Thohir , Lalu (Journal of Authentic Research, 2026)
This study aims to identify specific activities within the English Training Camp that contribute to improving students’ speaking skills and to explore students’ perceptions regarding the effectiveness of these activities at the Nurul Haramain Islamic Boarding School. A descriptive qualitative research design was employed. The participants consisted of three tutors and 15 students actively participating in the English Training Camp program, selected from a total population of 200 students. Data were collected through observation, interviews, and questionnaires, and subsequently analyzed using the stages of data reduction, data display, and conclusion drawing. The results indicate that the English Training Camp positively contributes to enhancing students’ speaking skills through the various activities organized, with "Tick Talk" identified as the most effective activity. These activities help students improve their English speaking abilities through daily speaking practice, competitions, and the "Super Camp" program. Furthermore, students held positive perceptions of the English Training Camp—with 84.67% of responses categorized as positive—attributing this to the program’s supportive learning environment, tutor guidance, and opportunities for active English practice in daily communication. Among the activities conducted, "Tick Talk"—part of the Super Camp program—was deemed the most effective for boosting students’ speaking skills and self-confidence. The study implies that non-formal language programs featuring structured communicative activities can serve as an effective model for developing speaking skills within an Islamic boarding school setting.